Aramaica Qumranica : proceedings of the conference on the Aramaic texts from Qumran at Aix-en-Provence (June 30-July 2, 2008) - Berthelot, Katell.; Stökl Ben Ezra, Daniel, 1970- (Studies on the Texts of the Desert of Judah, 2010)
The Aramaic Dead Sea Scrolls represent roughly 13% of the Qumran library and correspond to a wide range of genres and topics. This book consists of the proceedings of a conference on the Aramaic scrolls from Qumran which took place in Aix-en-Provence in 2008. It includes both the papers themselves and a transcription of the discussions. The 22 papers tackle linguistic, exegetical and historical questions, focusing in particular on: the relation of the Aramaic texts to what we know as the Hebrew Bible; their literary genres; the question of their sectarian or non-sectarian provenance; the character of the corpus, and specifically its relevance to the development of apocalypticism and messianism in the Jewish tradition.